Exponence, allomorphy and haplology in the number and State morphology of Modern Hebrew. Issue 1 (18th April 2018) - Faust, Noam
Abstract : This paper provides an account of the regularities of plural exponence in Modern Hebrew. There are two genders in Modern Hebrew, each with its specific plural marker. Nouns can appear in the Construct or Free states, and the State of a noun also has an effect on the plural marking, though only in the case of masculine nouns. Finally, in nouns with possessive suffixes and in newly-formed dual nouns, plural number seems to be marked twice in the feminine noun, but only once in the masculine noun. The analysis first formalizes the distribution of the plural allomorphs of gender and State in the language using the Vocabulary Items of Distributed Morphology (Halle & Marantz 1993 ). It is then claimed that the morpho-syntactic structures of N+possessive and of new duals involve two number projections, and therefore two plural exponents are expected in both constructions. However, in the masculine case the vocabulary Items provided in the paper result in the repetition of two overly similar exponents, creating an OCP violation. The repair is to delete one of the two, and so the double marking does not survive in the phonetic form. In the feminine case the two markers are not similar, and so there is no OCP violation, and double marking is surface-true.